Um olhar sobre o programa de formação continuada do Museu DICA: memória e identidade - Alves, Sabrina Eleutério (2019)
Teacher education is not limited to their initial education (undergraduate degree), but it is necessary to continuously build knowledge and skills for their teaching practice (CARRASCOSA, 1996; FERREIRA; SANTOS, 2016). From this perspective, it is believed that continuing in-school training can be a good for the teacher to fill in the gaps left by graduation. The purpose of this work was to understand the process of consolidation of the training program of the Museum DICA, seeking to highlight its identity, in order to leave a record that could support the trainers for the next courses. This work is characterized as a qualitative research and the method of data construction used was document analysis and semi-structured interviews (LÜDKE and ANDRÉ, 1986). The sample consisted of seven courses conducted from 2011 to 2018 and the intention was to investigate the potentialities, weaknesses and challenges faced by them. To facilitate our reflections on the seven courses taken at DICA, the following categories of analysis were created: (i) The Course Structure, (ii) The Course Theme, (iii) Teaching Resources and Methodologies used and / or discussed in the courses and (iv) The Data Building Instruments. In general, it was noticed that the courses analyzed brought varied discussions, regarding methodologies, contents and didactic resources and that the actions developed during the meetings demonstrated to contribute to the formation of the participating teachers, based on their reports extracted from the documentary analysis and presented in this paper. After the reflections, it was set out to build the product of this work, THE DICA’S TIPS: Memories Book of the DICA Museum Continuing Education Program, in order to present the memories of the courses already taken and promote an environment of dialogue with the students, future trainers. In this memoir, it is concerned with outlining the structure of meetings, structured data-building instruments and supporting tools that can assist in carrying out future actions. The opportunity to test some elements of this product in the teacher training course occurred from April to June 2019 by the DICA Museum in partnership with UFTM called “Problematizing the teaching of modern physics: radioactivity”. This test occurred in order to provide possible adjustments and modifications to the instruments to be incorporated into The DICA’s Tips. The reflections and actions of this work will be left as a supporting document for the DICA Museum team and may impact the museum's continuing education program, in a positive way, thus expanding the dialogue with the teacher.